KAJIAN PUPUK BOKASHI KOTORAN SAPI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L.): Kata kunci: Pupuk Bokashi Sapi, kacang hijau , pupuk NPK Phonska - jamshid, Ilham Maulana Jamshid; Sumarmi, Sumarmi; Siswadi, Siswadi (innofarm, 2023)
The study of Dosage of Cow Manure Bokashi Fertilizer and Phonska NPK Fertilizer on the Growth and Yield of Green Beans (Vigna radiata L.) was carried out December 2022 – March 2023 at the Tohudan Horticultural Seed Garden, Colomadu, Karanganyar. The purpose of this study was to determine the effect of NPK Phonska fertilizer and Bokashi Cow Manure on the growth and yield of green bean plants. A completely randomized design (RAKL) with two treatment factors and 16 treatment combinations repeated three times was used in the investigation. First factor (1) Bovine bokashi fertilizer (P) with 4 levels: control (P0) dose of 0 gram/plot, (P1) dose of 0.72 kg/plot, (P2) dose of 1.44 kg/plot, (P3) dose of 2.16 kg/plot . (2) Phonska NPK fertilizer (N) with 4 levels: control (N0), dose of 0 g/plot, (N1) dose of 14.4 grams/plot, (N2) dose of 28.8 grams/plot, (N3) dose of 28.8 grams/plot. The F test through analysis of variance and the BNJ test at the 5% level were both used to analyze the data. Parameters measured were plant height, number of leaves, weight of dry stover, number of pods planted, weight of newly planted pods, number of seeds per plot, and weight of 100 seeds. The results showed that cow bokashi fertilizer had an effect on plant height, number of leaves, weight of 100 seeds sown, and seed weight. Plant height, number of leaves, dry stover, seed weight per plant, seed weight per plot, and weight of 100 seeds were influenced by application of NPK fertilizer.